Microstructure, mechanical property and deformation behavior of Al0.33CrFeNi medium entropy alloys - Ling Qiao; Junya Inoue; Jingchuan Zhu (Journal of Materials Research and Technology, 2025)
A comprehensive understanding of dynamic deformation mechanisms is constrained by technological limitations in achieving real-time, atomic-level observation of microstructural evolution. This study used conventional experimental methods combined with molecular dynamics (MD) simulations to investigate the mechanical behavior of Al0.33CrFeNi MEAs. This alloy showed typical dendritic structure with random crystallographic orientations. The average modulus and hardness were measured to be 193.4 GPa and 6.02 GPa, respectively. Al0.33CrFeNi MEAs showed excellent plasticity at room temperature. The dendritic stem underwent significant deformation with preferred orientation of {001}, while it experienced slight deformation within the grain with relatively random orientation. Until 600 °C, it showed high strength good work hardening ability, simultaneously maintaining superior plasticity. The deformation is dominated by dislocation activity at lower temperature with a strong crystallographic texture. The dendrites exhibited preferred orientations of {111} at 200 °C. Based on the experimental EBSD evidence, the dynamic recovery and recrystallization occurred at temperature above 200 °C. The recrystallization was completed at 800 °C and grain growth occurs during deformation, with a strong preferred crystallographic orientation of {101}. The dominant deformation mechanism transitioned from dislocation glide to dynamic recrystallization and deformation twin as temperature increased. Our findings offered critical insights into the interplay between microstructural features and underlying deformation mechanisms in Al0.33CrFeNi MEAs.